Primary Angioplasty in a Catastrophic Presentation: Acute Left Main Coronary Total Occlusion—The ATOLMA Registry - A. Gutiérrez-Barrios; L. Gheorghe; S. Camacho-Freire; F. Valencia-Serrano; D. Cañadas-Pruaño; G. Calle-Pérez; I. Alarcón de la Lastra; E. Silva; D. García-Molinero; A. Agarrado-Luna; R. Zayas-Ruedas; R. Vázquez-García; et al. (Journal of Interventional Cardiology)
Objectives. To determine the outcome predictors of in-hospital mortality in acute total occlusion of the left main coronary artery (ATOLMA) patients referred to emergent angioplasty and to describe the clinical presentation and the long-term outcome of these patients. Background. ATOLMA is an uncommon angiographic finding that usually leads to a catastrophic presentation. Limited and inconsistent data have been previously reported regarding true ATOLMA, yet comprehensive knowledge remains scarce. Methods. This is a multicenter retrospective cohort that includes patients presenting with myocardial infarction due to a confirmed ATOLMA who underwent emergency percutaneous coronary intervention (PCI). Results. In the period of the study, 7930 emergent PCI were performed in the five participating centers, and 46 of them had a true ATOLMA (0.58%). At admission, cardiogenic shock was present in 89% of patients, and cardiopulmonary resuscitation was required in 67.4%. All the patients had right dominance. Angiographic success was achieved in 80.4% of the procedures, 13 patients (28.2%) died during the catheterization, and the in-hospital mortality rate was 58.6% (27/46). At one-year and at the final follow-up, 18 patients (39%) were alive, including four cases successfully transplanted. Multivariate analysis showed that postprocedural TIMI flow was the only independent predictor of in-hospital mortality (OR 0.23, (95% CI 0.1–0.36), p<0.001). Conclusions. Our study confirms that the clinical presentation of ATOLMA is catastrophic, presenting a high in-hospital mortality rate; nevertheless, primary angioplasty in this setting is feasible. Postprocedural TIMI flow resulted as the only independent predictor of in-hospital mortality. In-hospital survivors presented an encouraging outcome. ATOLMA and left dominance could be incompatible with life.